Hanukkah - Dickmann, Nancy (Chicago : Heinemann Library, 2011)
Simple text and photographs describe the story of Hanukkah and how the holiday is traditionally celebrated.
What is a festival? -- The story of Hanukkah -- Lighting candles -- Celebrating Hanukkah today -- Look and see.
Includes index.
1.6
K-3.
K-3
Keywords: Hanukkah -- Juvenile literature; Hanukkah; Hanukkah; Readers (Elementary).